Minimasi Pajak sebagai Pemoderasi pada Pengaruh Kontrak Utang, Mekanisme Bonus, dan Koneksi Politik - Gresella Cahya Endarta; Sri Luayyi; Fitria Magdalena (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of debt covenant, bonus mechanism, and political connections on tax avoidance with tax minimization as a moderating variable. The study uses secondary data from annual reports of energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The analysis method employed is Moderated Regression Analysis (MRA). The results show that debt covenant has a positive and significant effect on tax avoidance, while bonus mechanism and political connections have no significant effect. Furthermore, tax minimization is proven to moderate the relationship between debt covenant, bonus mechanism, and political connections on tax avoidance. The limitations of this study include the restricted sample scope limited to the energy sector and the limited number of variables used. Future research is recommended to expand the sample and include additional variables to obtain more comprehensive results.